MicroRNAs: Important Players in Breast Cancer Angiogenesis and Therapeutic Targets - Hussen, Bashdar Mahmud; Abdullah, Sara Tharwat; Rasul, Mohammed Fatih; Salihi, Abbas; Ghafouri-Fard, Soudeh; Hidayat, Hazha Jamal; Taheri, Mohammad (Frontiers in Molecular Biosciences, 2021)
The high incidence of breast cancer (BC) is linked to metastasis, facilitated by tumor angiogenesis. MicroRNAs (miRNAs or miRs) are small non-coding RNA molecules that have an essential role in gene expression and are significantly linked to the tumor development and angiogenesis process in different types of cancer, including BC. There's increasing evidence showed that various miRNAs play a significant role in disease processes; specifically, they are observed and over-expressed in a wide range of diseases linked to the angiogenesis process. However, more studies are required to reach the best findings and identify the link among miRNA expression, angiogenic pathways, and immune response-related genes to find new therapeutic targets. Here, we summarized the recent updates on miRNA signatures and their cellular targets in the development of breast tumor angiogenetic and discussed the strategies associated with miRNA-based therapeutic targets as anti-angiogenic response.